The Evolution of AI-Enhanced Automotive Infotainment: Technical Perspectives - Ravinder Katla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The evolution of automotive infotainment systems through artificial intelligence integration represents a fundamental transformation in human-vehicle interaction. Modern vehicles have transcended their transportation role to become sophisticated technological ecosystems where AI technologies address longstanding challenges in user experience, cognitive load management, and driver safety. This technical perspective explores the multilayered architectural framework underpinning these systems, from dedicated hardware accelerators and virtualized operating systems to sophisticated middleware and continuously learning AI models. The implementation of natural language processing capabilities utilizing far-field microphone arrays and domain-specific language models has dramatically improved voice interaction in challenging acoustic environments. Predictive capabilities leveraging recurrent neural networks and contextual awareness enable personalized experiences while reducing manual interactions. Safety enhancements through driver monitoring systems, dynamic workload management, and multimodal feedback pathways significantly reduce distraction and improve reaction times. Despite substantial resource constraints in computational power, thermal management, and energy efficiency, innovative solutions including model compression, selective activation strategies, and privacy-preserving computation techniques have emerged to address these challenges while maintaining functional safety compliance and robust offline capabilities.
Keywords: Automotive infotainment; artificial intelligence; driver monitoring; natural language processing; predictive computing